Motsure Hotsure Tsumugu - Duyvendijk, Marco van 1974-; Richards, Lynne (Marco van Duyvendijk, 2016)
This book tells the story of the kimonos of the Japanese island Amami. It shows the beauty of these kimonos and the skill and experience of the people that make them. It is a book about a quiet world full of craft, knowledge and dedication. Motsure Hotsure Tsumugu is nominated for the Anamorphosis Prize 2016. - 80 pages and two mini books with 12 pages each
Keywords: Duyvendijk, Marco van -- 1974-; Kimono; Fotografie; Bildband